Simulation of Electric Scooter Frame with Broadtrack Model Using Finite Element Method - Febritasari, Rosadila; Budi Mahardika, Ajiman; Astana Widi, I Komang; Arif Sutrisno, Tito; Dwi Korawan, Agus (Universitas PGRI Kanjuruhan Malang, 2024)
The frame is a main component for electric scooter construction which must have high distortion resistance to minimize the failure risk. This study aims to design a frame for electric scooter with broadtrack model and 1200 W of wheel drive motor power. The simulation was conducted by Finite Element Method (FEM) using Aluminum 6061 and Steel AISI 1020 as the material frame. The down tube used rectangular profile pipe and others used cylindric profile. The frame was generated in 3D model and been analysed using static structural. The results showed the biggest maximum stresses and also the smallest deformation given by steel AISI 1020 are 84,852 Mpa and 0.1082 mm, respectively. The minimum safety value for AISI 1020 steel material is 2.3813 and 6061 aluminum alloy is 1.5518. These show that the effect of mechanical properties on steel AISI 1020 is better than aluminum 6061. Overall, the Electric scooter frame should be recommended using steel AISI 1020.